Introduction to engineering experimentation - Wheeler, Anthony J (Pearson/Prentice Hall, 2004)
This text covers the most common elements necessary to design, execute, analyze, and document an engineering experiment or measurement system and to specify instrumentation for a production process. In addition to descriptions of common measurement systems, the text covers computerized data acquisition systems, common statistical techniques, experimental uncertainty analysis, and guidelines for planning and documenting experiments